Evaluation of forest cover change using remote sensing techniques and landscape metrics in Moncayo Natural Park (Spain). (August 2015) - Martinez del Castillo, Edurne; García-Martin, Alberto; Longares Aladrén, Luis Alberto; de Luis, Martin
Abstract: Monitoring the change in land cover in natural places, such as ecotones, has become an important tool for forest management, especially in protected areas. The present work analyses the spatial and temporal changes in forest cover in Moncayo Natural Park (Spain) from 1987 to 2010 using remote sensing techniques, geographical information systems (GIS) and quantitative indices of landscape ecology. Four Landsat images were used to map nine representative land cover categories in this preserved area in both years. The overall classification accuracies in land cover cartographies in 1987 and 2010 were 87.65% and 84.56%, respectively. Landscape metrics obtained at the landscape level show an increase in fragmentation and, as a result, an increase in landscape spatial diversity. Focusing on the class level, the results show a forest expansion of sessile oaks ( Quercus petraea ) and beech forest ( Fagus sylvatica ), two important bioclimatic indicators in this natural park, because they are the southernmost locations for these species in Europe. The decrease of mainly introduced pine forest and the transformation of mixed shrub areas into natural forested areas explain the aforementioned increase in fragmentation. These results are in agreement with the strategies for nature conservation designed by forest managers during the period evaluated. Highlights: Landscape heterogeneity, fragmentation and connectivity were analysed. Digital classification shows that the forested area changed over the last 23 years. The forest expansion was caused by land abandonment and forest management policies. Fragmentation increased, connectivity decreased, and heterogeneity remained equal. Forest quantitative information is needed by managers to assess their actions.